The Effect of Problem Focused Coping on Anxiety and Stress of Nursing Students During Online Learning - Yusup, Rian Maulana; Musharyanti, Lisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of problem-focused coping on nursing students' anxiety and stress during online learning. This research method uses a quasi-experimental method with a pretest-posttest design with a control group. The results showed that most of the experimental group's initial anxiety was moderate (35.5%) and the control group was also moderate (35.5%). Most of the anxiety in the experimental group is normal and mild (29.0%) and the control group is moderate (41.9%). Most of the initial stress in the experimental group was moderate (61.3%) and the control group was also moderate (51.6%). Most of the final stress in the experimental group was normal and moderate (32.3%) and the control group was moderate (38.7%). There is an effect of the problem-focused coping method on anxiety (ï² = 0.001) and stress (ï² = 0.000) in nursing students in online learning. The conclusion from this study is that the problem-focused coping method in academic guidance can be used as a method for reducing anxiety and stress in students, especially students during online learning. Keywords: Anxiety, Online Learning, Problem Focused Coping, Stress